Packet loss recovery in audio multimedia streaming by using compressive sensing. Issue 4 (1st March 2016) - Ciaramella, Angelo; Giunta, Giulio
Abstract : The aim of this study is to introduce a new scheme, based on a compressive sampling technique, for the reconstruction of lost data in multimedia streaming. The audio streaming data are encapsulated in different packets, at the sender, by using an interleaving technique. The compressive sampling technique is used to recover audio information in case of lost packets, at the receiver. Experimental results are presented for speech and musical audio signals which illustrate the performances and the capabilities of the proposed methodology.